2023
DOI: 10.1186/s12967-023-04318-w
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a clinic machine-learning nomogram for the prediction of risk stratifications of prostate cancer based on functional subsets of peripheral lymphocyte

Abstract: Background Non-invasive risk stratification contributes to the precise treatment of prostate cancer (PCa). In previous studies, lymphocyte subsets were used to differentiate between low-/intermediate-risk and high-risk PCa, with limited clinical value and poor interpretability. Based on functional subsets of peripheral lymphocyte with the largest sample size to date, this study aims to construct an easy-to-use and robust nomogram to guide the tripartite risk stratifications for PCa. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In 2021, Liang et al [ 7 ] reported good performance in predicting PCa malignancy using a multiparametric radiomic model and a combined clinical-radiomic model. More recently, in 2023, Yang et al [ 8 ] demonstrated good performance in predicting PCa risk stratifications based on functional subsets of peripheral lymphocytes. However, these studies were limited by the relatively small size of the clinical datasets used and did not offer a tripartite risk stratification.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Liang et al [ 7 ] reported good performance in predicting PCa malignancy using a multiparametric radiomic model and a combined clinical-radiomic model. More recently, in 2023, Yang et al [ 8 ] demonstrated good performance in predicting PCa risk stratifications based on functional subsets of peripheral lymphocytes. However, these studies were limited by the relatively small size of the clinical datasets used and did not offer a tripartite risk stratification.…”
Section: Introductionmentioning
confidence: 99%